Comparison of a polyvinyl chloride tube with a wire-reinforced tube for tracheal intubation through the SaCoVLM video laryngeal mask airway: protocol for a randomised controlled study - Min Zhang; Lina Chen; Weiwei Wang; Yuelan Wang; Zhongquan Gao; Yongle Guo; Xiaojun Gao; Meng Jie Liu; Xiaoning Zhang; Yongtao Sun (BMJ Open)
Introduction The SaCoVLM is a new type of video intubating laryngeal mask airway (LMA), and it is the first LMA to realise continuous visual monitoring. There is a lack of studies on intubation using the SaCoVLM. The aim of this study is to compare the success rate of intubation with polyvinyl chloride (PVC) tubes and wire-reinforced (WR) tubes using the SaCoVLM.Methods and analysis This prospective, single-centre, single-blind, parallel-arm, randomised controlled study will be conducted in a tertiary university hospital in China. We will include 104 patients undergoing elective laparoscopic surgery under general anaesthesia. Patients will be randomly assigned to the PVC tracheal tube group (n=52, PVC group) or the WR tracheal tube group (n=52, WR group). The primary outcome is the total success rate of intubation. The secondary outcomes are the first success rate of intubation, the time of tracheal intubation, the site of the first contact, the adjustment action for tracheal intubation, haemodynamic fluctuation during intubation and extubation, incidence of trauma as evidenced by blood, and the incidence rates of postoperative sore throat, hoarseness, and dysphagia.Ethics and dissemination This study was approved by the Ethics Committee of the First Affiliated Hospital of Shandong First Medical University (YXLL-KY-2022 (008)). All participants will provide written informed consent. The results will be disseminated through peer-reviewed publications and at conferences or congresses.Trial registration number NCT05338827.